2023
DOI: 10.1038/s41598-023-45987-3
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation and modelling of the mechanical properties of palm oil fuel ash concrete using Scheffe’s method

Godwin Adie Akeke,
Philip-Edidiong Udo Inem,
George Uwadiegwu Alaneme
et al.

Abstract: This study explores the enhancement of mechanical properties in concrete blended with palm oil fuel ash (POFA) through Scheffe's optimization. The utilization of POFA as supplementary cementitious material in concrete has gained attention for its potential environmental benefits. Utilizing a (5,2) simplex-lattice design, a systematic approach is employed for optimizing mixture proportions based on response parameters. The laboratory tests to evaluate concrete's mechanical behavior were conducted using the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…At the point of ultimate load, the control specimens underwent brittle failure, breaking into two distinct pieces. In contrast, the PCB fibre-reinforced concrete specimens did not exhibit brittle failure and remained intact without separating into two halves 42 , 43 .
Figure 4 Tensile strength of PCB and SFPCB fibre-reinforced concrete mixes.
…”
Section: Resultsmentioning
confidence: 85%
“…At the point of ultimate load, the control specimens underwent brittle failure, breaking into two distinct pieces. In contrast, the PCB fibre-reinforced concrete specimens did not exhibit brittle failure and remained intact without separating into two halves 42 , 43 .
Figure 4 Tensile strength of PCB and SFPCB fibre-reinforced concrete mixes.
…”
Section: Resultsmentioning
confidence: 85%
“…GPC also offers environmental benefits by utilizing industrial by-products, reducing carbon dioxide emissions and improved resistance to chemical attack compared to conventional concrete. Overall, while both materials are essential in construction, GPC presents a promising alternative with improved performance and sustainability characteristics 41 , 42 .
Figure 2 Assessing the Properties of 1m 3 of PCC and GPC 37 .
…”
Section: Geopolymer Concrete (Gpc)mentioning
confidence: 99%
“…ANOVA helps determine if there are statistically significant differences in the means of mechanical properties (response) based on various factors like aggregate sizes, proportions of laterite, w/c and slump as shown in Tables 8 , 9 , and 10 for compressive strength, flexural strength and splitting tensile strength respectively. By partitioning the total variability into components attributed to different sources of variation, ANOVA helps to identify which factors have the most substantial impact on the concrete's mechanical strength performance 80 , 81 . The obtained computation results showed that there is statistical significance between the variables at a 95% confidence interval with a P value of 0.047, 0.023 and 0.013 for compressive, flexural, and splitting tensile strength respectively which is less than the critical value of 0.05.…”
Section: Results Discussion and Analysismentioning
confidence: 99%